Relationship between altitudes, morphological traits, and biochemical compositions of Coffea canephora Pierre ex A. Froehner in Temanggung, Indonesia - Pangestika, Intan Widya; Susilowati, Ari; Purwanto, Edi; Gunawan (Menara Perkebunan, 2025)
Among various edaphoclimatic factors influencing coffee bean quality, altitude is one of the primary factors that should be taken into account. This study aims to explore the relationship between altitude, morphological traits, and biochemical composition of robusta coffee in Temanggung Regency, the largest coffee-producing area in Central Java Province, Indonesia. Research sites were purposively selected and categorized into two altitude groups: GS, PS, and GN, located at circa 600 m a.s.l., and GT, WO, and TG, located at circa 900 m a.s.l. A total of 15 morphological traits were observed, consisting of eight vegetative and seven generative traits. Caffeine content was measured following the AOAC procedure using UV-Vis spectrophotometry, while brew acidity was evaluated using a pH meter. Several morphological traits of Temanggung robusta coffee demonstrated significant relationships with altitude. Canopy and stem diameter showed negative correlations with altitude, with correlation coefficients of -0.366 and  -0.408, respectively. Conversely, fruit width               (r = 0.041), bean length (r = 0.049), and bean thickness (r = 0.047) exhibited positive correlations. Regarding biochemical composition, caffeine content stood out by displaying a strong positive correlation with altitude (r = 0.816). Additionally, several morphological traits, including the number of primary branches, the number of productive branches, the number of fruits per bunch, and traits related to fruits and beans, appear to be advantageous for selection and breeding programs. Understanding these relationships provides valuable insights for developing superior Temanggung robusta coffee plants adapted to specific altitudinal conditions.